ANALYSIS OF SCIENCE LITERACY ABILITY OF HIGH SCHOOL STUDENTS ON WORK AND ENERGY CONCEPT - Komariyah, Uyun; Nurlaela, Ai (Journal of Teaching and Learning Physics, 2023)
This study aims to determine the scientific literacy ability of class XI IPA students at SMAN 3 Kota Cilegon on the concept of work and energy. The method of the research used the descriptive quantitative method. The subjects of this study consisted of 145 students of class XI IPA. The research instrument used was a written test in the form of a description. Data analysis to find out the level of the students’ scientific literacy ability is done by giving them a raw score first on the whole questions. The raw scores acquired by the students are then changed into percentages. The results of this study found that the scientific literacy ability of class XI IPA students in the three domains of context, competencies, and knowledge was 51,76% with a very low category, then on the domain of attitudes got a percentage of 66,95% with a good attitude category. This study can help physics teachers measure the scientific literacy ability of students, so the information gained from this study can become an evaluation and an improvement in the study of physics at school.